Entrepreneurial Skills and Financial Access: The Mediating Role of Entrepreneurship Education in Shaping Entrepreneurial Interest - Irsyad Kamal; Kurnia Khafidhatur Rafiah; Salim Diarra (Indonesian Journal of Business and Entrepreneurship Research, 2025)
Student entrepreneurial interest is very important to encourage economic growth through job creation. This study aims to analyze the effect of entrepreneurial skills and access to capital on entrepreneurial interest with entrepreneurship education as a mediating variable in Universitas Padjadjaran students. The research method used is quantitative with explanatory descriptive design. Data were obtained using a closed questionnaire distributed digitally through Google Form with a Likert scale to students, then analyzed using path analysis techniques to test the direct and indirect effects between variables. The results showed that entrepreneurial skills have a significant direct effect on entrepreneurial interest and entrepreneurship education. Entrepreneurship education is also proven to have a significant effect on entrepreneurial interest. However, entrepreneurship skills have no significant effect indirectly through entrepreneurship education, while access to capital has no significant effect either directly or indirectly. This study highlights the importance of developing entrepreneurial skills and strengthening practice-based entrepreneurship education programs to increase students' interest in becoming entrepreneurs. Support in the form of relevant training is also recommended to enrich students' skills in starting and running a business.